Pharmacological Evaluation and Preparation of Nonsteroidal Anti-Inflammatory Drugs Containing an N-Acyl Hydrazone Subunit - Ferreira de Melo, Thais Regina [UNESP] (2014)
A series of anti-inflammatory derivatives containing an N-acyl hydrazone subunit (4a-e) were synthesized and characterized. Docking studies were performed that suggest that compounds 4a-e bind to cyclooxygenase (COX)-1 and COX-2 isoforms, but with higher affinity for COX-2. The compounds display similar anti-inflammatory activities in vivo, although compound 4c is the most effective compound for inhibiting rat paw edema, with a reduction in the extent of inflammation of 35.9% and 52.8% at 2 and 4 h, respectively. The anti-inflammatory activity of N-acyl hydrazone derivatives was inferior to their respective parent drugs, except for compound 4c after 5 h. Ulcerogenic studies revealed that compounds 4a-e are less gastrotoxic than the respective parent drug. Compounds 4b-e demonstrated mucosal damage comparable to celecoxib. The in vivo analgesic activities of the compounds are higher than the respective parent drug for compounds 4a-b and 4d-e. Compound 4a was more active than dipyrone in reducing acetic-acid-induced abdominal constrictions. Our results indicate that compounds 4a-e are anti-inflammatory and analgesic compounds with reduced gastrotoxicity compared to their respective parent non- steroidal anti-inflammatory drugs.